Improved Harmony Search Algorithm with Chaos for Absolute Value Equation - Longquan Yong; Sanyang Liu; Shouheng Tuo; Kai Gao (Universitas Ahmad Dahlan, 2013)
In this paper, an improved harmony search with chaos (HSCH) is presented for solving NP-hard absolute value equation (AVE) Ax - |x| = b, where A is an arbitrary square matrix whose singular values exceed one. The simulation results in solving some given AVE problems demonstrate that the HSCH algorithm is valid and outperforms the classical HS algorithm (HS) and HS algorithm with differential mutation operator (HSDE).